PERDAGANGAN ORANG SECARA ILEGAL SEBAGAI KEJAHATAN TRANSNASIONAL: STUDI PERBANDINGAN PENGATURAN DI INDONESIA DAN ARAB SAUDI - Satiaputra, Ade Andrian; Risnandar, Ahmad; Firmansyah, Ihsan (Ensiklopedia Research and Community Service Review, 2025)
Efforts to eradicate human trafficking are efforts carried out by various parties. Trafficking in persons, as defined in international law, can occur for a variety of exploitative purposes. However, different forms of human trafficking are often combined in many studies, policies, and interventions. This research aims to determine the implementation and impact of international agreements regarding transnational crime, especially human trafficking, as well as understanding regulations related to human trafficking crimes in Indonesia and Saudi Arabia. This research is doctrinal or normative research, the data collection methods in this research are divided into primary and secondary data, but the focus is only on secondary data which includeslegal source materials. That thisresearch also highlights the effortsthat the Indonesian government has made through legislation and international cooperation, including being a member of Interpol, to eradicate this crime. However, despite various efforts that have been made, including the deployment of Police Attachés in several countries and extradition agreements and mutual legal assistance, cases of human trafficking in Indonesia continue to increase. The results of this research conclude that there is a need for an active role from all related parties and more steps. Increasing economic standards is a fundamental step to combat human trafficking which is increasingly systematic, organized and difficult to detect.Keywords: Human Trafficking, Transnational Crime, International Cooperation